The Concepts of Social Space and Social Value: An Interpretation of Clinical Nursing Practice in Vietnam - Hong T. P Huynh; Carol Windsor (Global Qualitative Nursing Research, 2022)
This research draws on broader inquiry that explores the construction of the spatial positioning of nurses in Vietnam and how power structures sustained that positioning. Observations and individual interviews were undertaken with 32 registered nurses. Analysis of participant data and relevant policy documents moved beyond coding to theorising and thus to the abstraction of key concepts. Social space and social value were significant concepts developed in the research. The concept of space reflected the ways in which nurses constantly engaged in processes of negotiation to embed a sense of control over their practice. The related concept of social value brought focus to a power structure whereby the fiscal priorities of health care managers reinforced a disconnect between the use and exchange values of nurses. An interpretation of power relations that underpinned the material and symbolic spaces in which nurses worked was framed within the historical context of Vietnam.